Kinerja Perawat Ruang Rawat Inap RSUD Tengku Sulung - Linda, Nuraliza May; Leonita, Emy; Hanafi, Ahmad; Hartono, Budi; Ismainar, Hetty (Universitas Batanghari Jambi, 2024)
The largest proportion of health workers in the hospital is nurses which is 50.79%. One of the performance indicators is seen from the provision of nursing care in the hospital, seen from the nursing care documentation for the last 3 years in 2020 by 30%, in 2021 by 40.3% and in 2022 by 50.8%. The purpose of this research was to analyse nurses performance in the aspects of quality, quantity, used of working time, teamwork and incentives. This research used a qualitative research approach method with a case study design. interviews, observation and documentation were conducted on 5 informants to produce accurate and complete data. Data analysis in this research was carried out by triangulation. The results of this research found that nurses' knowledge of SOPs was good. Incomplete documentation of the initial study on medical history was 40% and physical examination was 60%. Nurses’ activity time were still classified as low direct activities by 19.5%, indirect activities by 32.6%, personal activities by 28.9% and non-productive activities by 19.5%. Providing financial incentives in the form of Eid Mubarak THR, while non-financial incentives in the form of awards and praise have not been implemented. Teamwork is less effective due to the lack of pharmacists and nutritionists in collaboration. The performance of nurses in inpatient rooms are less effective because in the implementation of nursing SOPs there are still nurses who are not in accordance with SOPs, incompleteness in filling out the initial nursing review documentation, nursing activity time are still low, financial and non-financial incentives are not implemented and teamwork is less effective due to the lack of involvement between pharmacists and nutrition professionals in collaboration.